Making something happen : American political poetry between the world wars - Thurston, Michael, 1965- (Cultural studies of the United States., 2001)
This text looks back to the 1920s and 1930s to a generation of poets who wrote with the precise hope and the deep conviction that they would move their audiences to action. It offers a different look at the political poetry of Edwin Rolfe, Langston Hughes, Ezra Pound and Muriel Rukeyser.